Perilaku Hate Speech di Media Sosial Facebook dan Twitter (Studi Pada Mahasiswa Universitas Negeri Padang) - Maidila, Winda Putri; Moeis, Isnarmi; Suryanef, Suryanef; Hasrul, Hasrul (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2024)
This study investigates hate speech behavior on social media among students at Padang State University. Using a content analysis method with a qualitative approach, the study examines social media comments, particularly from Facebook and Twitter. Fourteen respondents were selected through purposive sampling to serve as informants. Data were collected through interviews and documentation, with analysis following stages of data collection, reduction, presentation, and conclusion drawing. The validity of the data was ensured through theory triangulation. Findings reveal that hate speech by UNP students took the forms of insults, fake news (hoaxes), and incitement. Contributing factors included individual emotional expression, the rapid and manipulative spread of information associated with globalization, lack of student awareness, political influences, and peer group dynamics. The study's limitations involve a small sample size, which may affect the generalizability of the results. Furthermore, data were sourced from only a few platforms, narrowing the scope of social media perspectives captured. Future research with a larger sample and more diverse platform sources would yield a more comprehensive view of this issue.